2020
DOI: 10.1177/1049732320944142
|View full text |Cite
|
Sign up to set email alerts
|

How Participatory Music Engagement Supports Mental Well-being: A Meta-Ethnography

Abstract: Participatory music engagement has the capacity to support well-being. Yet, there is little research that has scrutinized the processes through which music has an effect. In this meta-ethnography [PROSPERO CRD42019130164], we conducted a systematic search of 19 electronic databases and a critical appraisal to identify 46 qualitative studies reporting on participants’ subjective views of how participatory music engagement supports their mental well-being. Synthesis of first-order and second-order interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 88 publications
4
37
0
6
Order By: Relevance
“…In some cases, they waited the whole week for the session, and by attending it they strengthened links to their memories and identities. Both listening to and making music improved mood and stimulated attention and imagination, in agreement with other studies (Hays and Minichiello, 2005;Laukka, 2006;Lally, 2009;Costa et al, 2018a,b) that also show that music is often considered beneficial to wellbeing (Perkins et al, 2020). In addition, the program elicited positive emotions and represented a pleasant novelty because it offered the opportunity to listen closely to high quality live musical performances and to approach music making supported by and interacting with skilled musicians.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In some cases, they waited the whole week for the session, and by attending it they strengthened links to their memories and identities. Both listening to and making music improved mood and stimulated attention and imagination, in agreement with other studies (Hays and Minichiello, 2005;Laukka, 2006;Lally, 2009;Costa et al, 2018a,b) that also show that music is often considered beneficial to wellbeing (Perkins et al, 2020). In addition, the program elicited positive emotions and represented a pleasant novelty because it offered the opportunity to listen closely to high quality live musical performances and to approach music making supported by and interacting with skilled musicians.…”
Section: Discussionsupporting
confidence: 88%
“…The results are aligned with those of other studies (Hays and Minichiello, 2005;Creech et al, 2014;Perkins and Williamon, 2014;Yap et al, 2017) and are novel as they reflect the context of nursing homes, as participants reported also feelings of isolation, doubts about their own cognitive abilities, and a lack of novelty and engagement. The overall picture emerging confirms the idea that the benefits perceived from the engagement with music derive from complex processes, which include diverse dimensions largely influenced by idiosyncratic needs and circumstances (Perkins et al, 2020). In this case, as illustrated in Figure 1, the results suggest that this program has had mainly positive effects as it facilitated access to something considered important, offering learning opportunities and promoting interpersonal relationships in a context where novelty and engagement are sometimes missing.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Evidence on the role of arts and cultural engagement in promoting health and wellbeing is ever growing [12,21]. The relationship between arts engagement and mental health-in particular, wellbeing and depression-has been well-rehearsed in large-scale epidemiological data [2][3][4]20], studies on individual arts activities [22][23][24], and literature reviews [e.g., [25][26][27][28][29]. Despite the suggested importance of the connection between arts engagement and social outcomes specifically, and indications that the arts may play a role in preventing or alleviating loneliness and boosting social connectedness and social wellbeing [30][31][32][33], the arts have been less represented in large-scale epidemiological cohorts (compared with, for example, mental and physical health outcomes) and have been less frequently documented in empirical research.…”
Section: Relationships Between Arts Engagement and Social Wellbeingmentioning
confidence: 99%
“…Long-lasting detriment to public mental health is a reported consequence of critical importance (Brooks et al, 2020 ; Gonçalves et al, 2020 ). In the past decade, research has shown that various forms of musical engagement with others can positively impact on an individual's socioemotional well-being; this has been reported as an outcome of both specific interventions and other forms of participatory music-making (Hallam, 2010 ; Hallam et al, 2014 ; Wilson and MacDonald, 2019 ; Perkins et al, 2020 ) as well as of particular familial and cultural contexts on listening behavior (Packer and Ballantyne, 2011 ; Boer and Abubakar, 2014 ). More recently, qualitative research on group musical engagement during the COVID-19 pandemic has suggested that involvement in online musical interaction in educational and improvisational settings may positively impact on individuals' psychological well-being and communities' connectedness (de Bruin, 2021 ; MacDonald et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%